Pelvic desmoid tumour imitating uterine leiomyoma in a Nigerian premenopausal woman (2020)
Aim: To describe a rare case of pelvic desmoid tumour simulating as a huge uterine leiomyoma causing a diagnostic dilemma in a premenopausal woman. Case Presentation: This was a 44-year-old, para 2 (2 alive) who was referred to our gynaecology clinic from a secondary health facility on account of slowly increasing abdominal swelling of 2 years Case Report Ajani et al.; JAMMR, 32(2): 94-99, 2020; Article no. JAMMR.54612 95 duration. There was no nausea, vomiting or diarrhoea. There was associated mild to moderate dull lower abdominal pain that did not radiate to any other part of the body. There was no change in her monthly menstrual flow. Physical examination revealed a pelvic mass about 32 weeks pregnancy size and firm. Computed Topography scan showed a huge pedunculated sub-serous uterine fibroid. A huge mass adherent to the anterior surface of the body of the uterus was completely surgically excised at exploratory laparotomy. Histology of the excised tumour revealed a definitive histological diagnosis of pelvic desmoid tumour. The patient was clinically stable and discharged home 10 days post operation and was followed-up on out-patient gynaecology clinic basis. Discussion: Pelvic desmoid is a rare mesenchymal tumour caused by abnormal proliferation of fibroblasts. It is three times more common in women and occurs mostly between 25 and 35 years of age which correspond to the same age peak incidence for uterine fibroids. The tumour can easily be misdiagnosed as uterine leiomyoma and imaging cannot reliably distinguish the two conditions. Conclusion: Pelvic desmoid tumour should be considered as a differential diagnosis in premenopausal women who present with abdominal swelling. Relevant clinical history, Radiological imaging and Histopathological assessment are essential in making prompt accurate diagnosis.